The history of basilar artery occlusion: when art aids science - Francisco Antunes Dias; Daniel Giansante Abud; Octavio Marques Pontes-Neto (Arquivos de Neuro-Psiquiatria)
ABSTRACT Basilar artery occlusion (BAO) ischemic stroke is a relatively rare condition with high morbidity and mortality rates. To date, the best acute reperfusion therapy for BAO has still not been established, mainly due to the lack of randomized controlled trials in this field. In this article, we review the history of BAO diagnosis and treatment, and the impact of modern technological resources on the clinical evolution and prognosis of BAO over time. Furthermore, we describe historical events and nonmedical literature descriptions related to BAO. We conclude that BAO is a singular example of how art may help medical sciences with accurate descriptions of medical conditions.